Utilization of the YouTube platform as a distance learning media for the basic theory of music in junior high school - Muhamamd Alif Mukti; Asep Bayu Dani Nandiyanto; Tedi Kurniawan; Muhammad Roil Bilad (Universitas Pendidikan Indonesia, 2021)
The YouTube platform. The purpose of this study was to see students using YouTube as a learning media to increase students' interests and talents in the field of music. YouTube can be used as a practical learning tool that accommodates various materials in it. The method used is quantitative with data collection techniques using questionnaires as a data collection tool. The results of this study show an average pretest value of 49% to an average posttest value of 75% so the difference is 26%. Therefore, we can use YouTube as a distance learning media for the basic theory of music.